Optimalisasi Fungsi Masjid Sebagai Sarana Dakwah dan Pemberdayaan Ekonomi Umat - Bahtiar Effendi; Abdul Ghofar Saifudin (JIEF : Journal of Islamic Economics and Finance, 2022)
This research aims to find out how to optimize the function of the mosque as a means of da'wah and economic empowerment of the people. The subject of this research is the Assalam Mosque located in Rowosari Village, Ulujami District, Pemalang Regency. This research uses a descriptive qualitative method. Data analysis by triangulation, data obtained through observation and interviews with informants of the management and congregation of the Assalam Mosque. The results show that, apart from functioning as a place of worship, Masjid Assalam seeks to optimize its other functions as a center for da'wah for youth, youth and adult congregations. Other part carried out at the Assalam Mosque are social functions in distributing rice alms to pilgrims, collecting and distributing aid to disaster victims, and economic empowerment to stalls and shops owned by pilgrims.